The complete chloroplast genome of the ornamental plant Primula violaris (Primulaceae). Issue 12 (2nd December 2021) - Chai, Weiguo; Li, Huimin; Zhang, Caijuan; Zhao, Bo; Xia, Pengguo
Abstract: Primula violaris is a perennial herb distributed throughout the western part of Hubei Province and the southern part of Shaanxi Province, China. We present on of the first reports of the complete chloroplast genome sequence for P. violaris . The complete chloroplast genome was 153, 630 bp in size, including a large single-copy (LSC) region of 84, 526 bp, a small single-copy (SSC) region of 17, 812 bp, and a pair of inverted repeat (IR) regions of 25, 646 bp. There were 130 genes in the chloroplast genome, including 86 CDSs, 36 transfer RNA (tRNA) genes, and eight rRNA genes. Phylogenetic analysis showed that P. violaris is closely related to P. oreodoxa . (NC_050848).